Early recognition of limb necrotizing fasciitis and surgery within six hours is associated with a lower mortality risk and improved patient-reported outcomes - Andrew D. Ablett; Chryssa Neo; Tony Feng; Nick D. Clement; Andrew D. Duckworth; Timothy O. White (Bone & Joint Open, 2026)
Aims Necrotizing fasciitis (NF) is a rapidly progressive surgical emergency. The effects of time from hospital presentation to theatre on short- and long-term outcomes, as well as specific modifiable aspects of the care pathway that would enable early surgery, remain poorly defined. Methods A retrospective cohort study of all suspected cases of limb NF presenting across a large health board region over ten years (January 2015 to April 2025) was undertaken. Early surgery was defined as ≤ six hours from presentation (triage time) to theatre (operation start time). The independent associations between surgical timing and 30-day mortality or amputation were assessed. A timeline analysis identified areas where delays occurred. Survivors completed the EuroQol five-dimension five-level questionnaire (EQ-5D-5L) and Toronto Extremity Salvage Score (TESS) outcome assessments. Results Of 359 referrals, four patients died prior to surgery and 80 patients underwent emergency surgery due to surgeon suspicion of NF. For cases of intraoperatively confirmed NF (n = 63/80), early surgery was associated with a five-fold reduction in 30-day mortality rate (overall rate 22% (n = 14/63); adjusted hazard ratio 0.19, 95% CI 0.04 to 0.87, p = 0.032; absolute risk difference 25%). Additionally, early surgery was associated with reduced rates of 30-day amputation (overall rate 30% (n = 19/63); adjusted hazard ratio 0.19, 95% CI 0.05 to 0.66, p = 0.009; absolute risk difference 32%). At a median of 27 months’ follow-up (IQR 16 to 48), only 35 patients (56%) were alive. Survivors having early surgery reported significantly better patient-reported outcomes (EQ-5D: 0.785 vs 0.133, p = 0.003; TESS combined: 64.9 vs 28.7, p = 0.007). Conclusion Early surgery for patients with NF was associated with a lower risk of mortality, amputation, and severe long-term disability. Early recognition and transfer to theatre represent modifiable targets for improving survival and outcomes. Cite this article: Bone Jt Open 2026;7(9):1126–1136.